Global hotspots and correlates of emerging zoonotic diseases. Issue 1 (December 2017) - Allen, Toph; Murray, Kris; Zambrana-Torrelio, Carlos; Morse, Stephen; Rondinini, Carlo; Di Marco, Moreno; Breit, Nathan; Olival, Kevin; Daszak, Peter
Abstract Zoonoses originating from wildlife represent a significant threat to global health, security and economic growth, and combatting their emergence is a public health priority. However, our understanding of the mechanisms underlying their emergence remains rudimentary. Here we update a global database of emerging infectious disease (EID) events, create a novel measure of reporting effort, and fit boosted regression tree models to analyze the demographic, environmental and biological correlates of their occurrence. After accounting for reporting effort, we show that zoonotic EID risk is elevated in forested tropical regions experiencing land-use changes and where wildlife biodiversity (mammal species richness) is high. We present a new global hotspot map of spatial variation in our zoonotic EID risk index, and partial dependence plots illustrating relationships between events and predictors. Our results may help to improve surveillance and long-term EID monitoring programs, and design field experiments to test underlying mechanisms of zoonotic disease emergence. The risk of epidemics originating from wild animals demands close monitoring of emerging infectious disease (EID) events and their predictors. Here, the authors update a global database of EID events, analyze their environmental and biological correlates, and present a new global hotspot map of zoonotic EID risk.